Nicotine-prevented learning and memory impairment in REM sleep-deprived rat is modulated by DREAM protein in the hippocampus - Abd Rashid, Norlinda; Hapidin, Hermizi; Abdullah, Hasmah; Ismail, Zalina; Long, Idris (2017)
Introduction: REM sleep deprivation is associated with impairment in learning and memory, and nicotine treatment has been shown to attenuate this effect. Recent studies have demonstrated the importance of DREAM protein in learning and memory processes. This study investigates the association of DREAM protein in REM sleep-deprived rats hippocampus upon nicotine treatment. Methods: Male Sprague Dawley rats were subjected to normal condition, REM sleep deprivation and control wide platform condition for 72 hr. During this procedure, saline or nicotine (1 mg/kg) was given subcutaneously twice a day. Then, Morris water maze (MWM) test was used to assess learning and memory performance of the rats. The rats were sacrificed and the brain was harvested for immunohistochemistry and Western blot analysis. Results: MWM test found that REM sleep deprivation significantly impaired learning and memory performance without defect in locomotor function associated with a significant increase in hippocampus DREAM protein expression in CA1, CA2, CA3, and DG regions and the mean relative level of DREAM protein compared to other experimental groups. Treatment with acute nicotine significantly prevented these effects and decreased expression of DREAM protein in all the hippocampus regions but only slightly reduce the mean relative level of DREAM protein. Conclusion: This study suggests that changes in DREAM protein expression in CA1, CA2, CA3, and DG regions of rat’s hippocampus and mean relative level of DREAM protein may involve in the mechanism of nicotine treatment-prevented REM sleep deprivation-induced learning and memory impairment in rats